1996
DOI: 10.1148/radiology.198.1.8539378
|View full text |Cite
|
Sign up to set email alerts
|

Posterolateral aspect of the knee: improved MR imaging with a coronal oblique technique.

Abstract: Depiction of the structures in the posterolateral aspect of the knee was optimal on coronal oblique images. We advocate obtaining coronal oblique T2-weighted images in patients with either posterolateral knee pain or suspected injury to the posterolateral ligamentous structures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
104
1
3

Year Published

1999
1999
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(110 citation statements)
references
References 0 publications
2
104
1
3
Order By: Relevance
“…In that study, using conventional MRI sequences, a surgical popliteofibular ligament injury went unnoticed on MRI in three cases. A thin-slice coronal oblique MRI sequence improved evaluation of the PLC [34]. In 20 knees with surgically verified Grade 3 PLC injuries evaluated with an MRI protocol including thinslice coronal oblique images through the fibular head, LaPrade et al [12] found MRI to be accurate in diagnosing FCL, popliteus, and popliteofibular ligament injury in 95%, 90%, and 68% of cases, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In that study, using conventional MRI sequences, a surgical popliteofibular ligament injury went unnoticed on MRI in three cases. A thin-slice coronal oblique MRI sequence improved evaluation of the PLC [34]. In 20 knees with surgically verified Grade 3 PLC injuries evaluated with an MRI protocol including thinslice coronal oblique images through the fibular head, LaPrade et al [12] found MRI to be accurate in diagnosing FCL, popliteus, and popliteofibular ligament injury in 95%, 90%, and 68% of cases, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…As a static study, MRI also has inherent limitations for diagnosing clinically relevant instability, and partial tears or edema revealed on MRI may not correlate with laxity [32]. High-power magnets [1,12], thinslice scans [12], and coronal oblique technique [1,12,34] have improved MRI of the PLC, but access to this technology and experienced musculoskeletal radiologists may not be universally available, particularly in community hospitals or clinics [23].…”
Section: Introductionmentioning
confidence: 99%
“…Angling the coronal plane is thought to decrease volume averaging that could potentially obscure structures. Detection of the fabellofibular ligament seems to be dependent on positioning of the knee rather than an oblique imaging plane [69].…”
Section: Fibular Collateral Ligamentmentioning
confidence: 95%
“…In addition, the presence of the arcuate and fabellofibular ligaments has been shown to be inconsistent in cadaveric studies [69].…”
Section: Fibular Collateral Ligamentmentioning
confidence: 99%
“…Some advocate the use of a coronal oblique plane, oriented parallel to the direction of the popliteus tendon, with one study showing visualization of the popliteofibular tendon improving from 8% to 53% of the knees. 63 Another study compared coronal oblique fat-saturated T2 with isotropic three-dimensional water excitation double-echo steady state (WE-DESS) sequences. The latter sequence improved the identification of the popliteofibular ligament from 71% to 91% of cases.…”
Section: 62mentioning
confidence: 99%